The Relationship between Health Anxiety and Prenatal Distress with Choosing Mode of Delivery among Pregnant Women During COVID-19 Epidemic: A Cross-Sectional Study - Maryam Beheshti Nasab; Hadis Bahmaei; Saeedeh Askari; Saeed Ghanbari; Mina Iravani (Journal of Midwifery & Reproductive Health, 2022)
Background & aims: Corona-Virus is a serious infectious disease that was rapidly spread worldwide and caused considerable anxiety among people. Pregnant women are more prone to increased anxiety caused by the Covid-19 epidemic. This study was performed to evaluate the relationship between health anxiety and prenatal distress with choosing mode of delivery among pregnant women during COVID-19 epidemic in Iran.Methods: This cross-sectional study was performed on 200 nulliparous pregnant women referred to the health centers of Ahvaz to receive the routine prenatal care. The questionnaires used were demographic, the health anxiety index-short form, and the prenatal distress questionnaire. At the end, the participants were asked by two questions whether their views on the mode of delivery has changed during COVID-19 epidemic.Results: A significant difference was observed between choosing mode of delivery before and after the onset of the covid-19 epidemic (P=0.012). Health anxiety and prenatal distress score was higher in women who selected cesarean section (P<001) after the onset of the epidemic. Also, the maternal concern for fetal health was significantly higher in mothers who chose cesarean section than in women who chose vaginal delivery (P=0.014).Conclusion: The findings of the current study showed that higher health anxiety and prenatal distress in pregnant women during the COVID-19 epidemic caused a significantly higher probability of selecting cesarean section as a mode of delivery. Therefore, it is very important to promote the mental health of pregnant women during the epidemic.